TARGETED DRUG DEVELOPMENT IN FRAGILE X SYNDROME: MOLECULAR MEDICINE AS A KEY TOOL IN CLINICAL PHARMACOLOGY - Protic, Dragana; Stojkovic, Maja; Budimirovic, Dejan (Medical Research, 2025)
The full mutation and epigenetic silencing of the FMR1 gene lead to a deficiency of its protein, FMRP, resulting in Fragile X Syndrome (FXS). Although significant advances have been made in understanding the molecular mechanisms underlying FXS, no cure or targeted pharmacological treatments have yet been approved for this neurodevelopmental disorder. Current clinical management primarily relies on symptomatic therapies, which often offer limited benefits and do not address the core molecular causes of the condition, especially given the multifaceted roles of the FMRP. This review highlights the crucial role of molecular insights in guiding the development of drugs for FXS. It provides an overview of existing pharmacotherapies, discusses their benefits and limitations, and emphasizes the unmet need for interventions that target the specific pathways disrupted by FMR1 dysfunction. Recent and ongoing clinical trials were examined, focusing on how a deeper understanding of FXS molecular biology can inform the design of more effective and precise therapeutic strategies. In summary, key molecular pathways relevant to FXS are presented, and the potential synergy between clinical pharmacology and molecular medicine is discussed as a means to promote the advancement of tailored therapeutic approaches.
Keywords: fragile X syndrome, pharmacotherapy, targeted treatment, FMR1 gene